Transcatheter aortic valve implantation using balloon-expandable Myval transcatheter heart valve in a patient with bicuspid aortic valve with low-flow, low-gradient severe aortic stenosis - Adhikari, Chandra Mani; Bogati, Amrit; Timalsena, Birat; Safi, Sajjad; Kharel, Sushant; Thapa, Pratik; Ghimire, Vijay; Yadav, Rahul; Khan, Barkadin; Prajapati, Dipanker (Nepalese Heart Journal, 2024)
Transcatheter aortic valve implantation is the most preferred treatment for aortic stenosis in elderly patients at high surgical risk. We share our experience with Transcatheter aortic valve implantation utilizing a balloon-expandable Myval transcatheter heart valve in a patient diagnosed with a bicuspid aortic valve, exhibiting low-flow, low-gradient severe aortic stenosis, along with annular calcification that extends to the left ventricular outflow tract and horizontal aorta.